\(\displaystyle{6}{x}^{{{2}}}-{5}{x}+{1}\)

\(\displaystyle{a}={6}{b}=-{5}{c}={1}\)

1. \(\displaystyle{a}{c}={6}={2}\times{3}\times{1}.\)

2. \(\displaystyle-{2}\pm{3}=-{5}={b}\)

3. \(\displaystyle{6}{x}^{{{2}}}-{5}{x}+{1}={6}{x}^{{{2}}}-{2}{x}-{3}{x}+{1}\)

4. \(\displaystyle{6}\cdot{2}{x}{\left({3}{x}-{1}\right)}-{1}{\left({3}{x}-{1}\right)}{G}{C}{F}={\left({3}{x}-{1}\right)}\)

5. \(\displaystyle{\left({2}{x}-{1}\right)}{\left({3}{x}-{1}\right)}\)

\(\displaystyle{a}={6}{b}=-{5}{c}={1}\)

1. \(\displaystyle{a}{c}={6}={2}\times{3}\times{1}.\)

2. \(\displaystyle-{2}\pm{3}=-{5}={b}\)

3. \(\displaystyle{6}{x}^{{{2}}}-{5}{x}+{1}={6}{x}^{{{2}}}-{2}{x}-{3}{x}+{1}\)

4. \(\displaystyle{6}\cdot{2}{x}{\left({3}{x}-{1}\right)}-{1}{\left({3}{x}-{1}\right)}{G}{C}{F}={\left({3}{x}-{1}\right)}\)

5. \(\displaystyle{\left({2}{x}-{1}\right)}{\left({3}{x}-{1}\right)}\)